A covert complication of arteriovenous fistulas. Issue 5 (May 2015) - Imran, Tasnim F.; Hashim, Hayder; Beidas, Abdel-Kareem; Oriscello, Ralph
Abstract Our patient is a 65-year-old man with a history of hypertension, aortic stenosis, and end-stage renal disease on hemodialysis who presented with worsening dyspnea. On examination, he exhibited signs of volume overload and had a radiocephalic arteriovenous fistula (AVF) with a significantly palpable thrill. Coronary angiogram showed normal coronary arteries. Cardiac catheterization revealed a cardiac output of 10.6 L/min by thermodilution. Ultrasound of the AVF access demonstrated an abnormally high velocity with flow >5 L/min. The patient was diagnosed with high-output heart failure (HOHF) secondary to his arteriovenous fistula. HOHF is an uncommon entity associated with certain pathologic states such as hyperthyroidism, skeletal and dermatologic disorders. It is defined as a high cardiac output >8 L/min, resting cardiac index >2.5–4.0 L/min per m2, and low systemic vascular resistance. Cardiac catheterization is often required for definitive diagnosis. The increased cardiac output may result in overt heart failure in patients with underlying heart disease. Treatment of HOHF secondary to an extracardiac shunt involves flow reduction procedures, ligation, or peritoneal dialysis. Our patient was successfully treated with AVF banding. Early recognition of this complication is critical, as many cases are reversible. <Learning objective: High-output heart failure, defined as cardiac output >8 L/min, resting cardiac index >2.5–4.0 L/min per m2 and low systemic vascular resistance, is an uncommon entity associated with conditions such as hyperthyroidism, skeletal disorders, and dermatologic disorders. It is an often-missed complication in patients with arteriovenous fistulas, particularly those with underlying heart disease. The Kidney Foundation guidelines recommend arteriovenous fistula monitoring by physical examination and monthly flow measurements for patients at risk.>